SWOT Analysis of the Development Strategy of Annisa Taylor as a Waqf Business Unit at Darussalam Gontor for Girls First Campus - Suarni Ukas; Tri Intan Ristantanti; Zaskia Calista Ardelia; Andi Triyawan (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Pondok Modern Darussalam Gontor is one of the institutions that is considered successful in productive waqf management. Annisa Taylor as one of the waqf business units at PMDG Putri 1 has a very important role in economic development. The purpose of this research is to analyze the development strategy of the taylor waqf business unit at Pondok Modern Darussalam Gontor based on SWOT analysis. This research plan uses a qualitative descriptive method. This method discusses the results obtained from direct visits, interviews, and literature reviews which are then used as conclusions in the formulation of existing problems. The results of this study indicate that the Annisa Taylor sector has: strengths (s) making clothes according to consumer desires, no shortage of labor (employees), distributing goods to alumni lodges, and cooperating with management in improving human resources; weaknesses (w) unable to follow trends, less space for production, human resources in quality have not met market needs, sizes that do not meet demand, do not have appreciation or appreciation; opportunity (o) producing more goods when the Drama Arena or Panggung Gembira event is held, more income at the beginning of the year (influx of prospective students), the existence of alumni huts, putting production goods for sale in mini markets or Latansa depots; threat (t) busy activities, embroidery sewing machines that hamper the quality of labor.